Enhancing community and environmental resilience through landscape management in Ethiopia - Mekuria, Wolde; Haileslassie, Amare (International Water Management Institute, 2024)
This brief summarizes key recommendations from a decade of research to help overcome some of the governance challenges that hinder the effective implementation of landscape management practices. This study was supported by projects, such as the European Union’s Supporting Horn of Africa Resilience (SHARE) I and II projects, and the Nature-Based Solutions for Sustainable and Inclusive Development (NSSID) program which is built on the outputs of the Growth for Future (G4F) project. At the onset, the brief describes the concepts of landscape and landscape management. Thereafter, the context, policy actions and gaps in agricultural landscape management in Ethiopia are explained followed by the findings on landscape management practices such as PFM, freshwater ecosystem conservation, protected area management, hydro-sediment monitoring, and changes in ESVs due to land conversion relating to the ecoregional development framework are detailed. Lastly, the brief provides recommendations for policymakers and other stakeholders to build community and environmental resilience, giving due consideration to diverse practices that benefit both humans and nature.